Age‐related reduction in the expression of FOXO transcription factors and correlations with intervertebral disc degeneration. Issue 12 (4th May 2017) - Alvarez‐Garcia, Oscar; Matsuzaki, Tokio; Olmer, Merissa; Masuda, Koichi; Lotz, Martin K.
ABSTRACT: Aging is a main risk factor for intervertebral disc (IVD) degeneration, the main cause of low back pain. FOXO transcription factors are important regulators of tissue homeostasis and longevity. Here, we determined the expression pattern of FOXO in healthy and degenerated human IVD and the associations with IVD degeneration during mouse aging. FOXO expression was assessed by immunohistochemistry in normal and degenerated human IVD samples and in cervical and lumbar IVD from 6‐, 12‐, 24‐, and 36‐month‐old C57BL/6J mice. Mouse spines were graded for key histological features of disc degeneration in all the time points and expression of two key FOXO downstream targets, sestrin 3 (SESN3) and superoxide dismutase (SOD2), was assessed by immunohistochemistry. Histological analysis revealed that FOXO proteins are expressed in all compartments of human and mouse IVD. Expression of FOXO1 and FOXO3, but not FOXO4, was significantly deceased in human degenerated discs. In mice, degenerative changes in the lumbar spine were seen at 24 and 36 months of age whereas cervical IVD showed increased histopathological scores at 36 months. FOXO expression was significantly reduced in lumbar IVD at 12‐, 24‐, and 36‐month‐old mice and in cervical IVD at 36‐month‐old mice when compared with the 6‐month‐old group. The reduction of FOXO expression in lumbar IVD was concomitant with a decrease in the expression of SESN3 and SOD2. These findings suggest that reduced FOXO expression occurs in lumbar IVD during aging and precedes the major histopathological changes associated with lumbar IVD degeneration. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2682–2691, 2017.